UNPACKING FLEXIBILITY: THE IMPACT OF FLEXIBLE WORK ARRANGEMENTS ON EMPLOYEE WELL-BEING, SATISFACTION, AND PERFORMANCE IN THE IT SECTOR - Kaur, Karamwant; Dharamveer (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Flexible Work Arrangements (FWAs) have emerged with high visibility in reshaping modern organizational practice, especially in knowledge-intensive industries like Information Technology (IT). This study considers the different types of flexible work arrangements employed in the Indian IT industry and analyzes their implications on key employee outcomes like productivity, job satisfaction, and work-life balance. Data were collected from 115 IT professionals who completed a structured questionnaire. The findings suggest that flexible work patterns like teleworking, flexitime, compressed workweek, and hybrid arrangements are common and are largely thought to be positive for individual performance and job satisfaction. Yet, despite these perceived benefits, the study also finds difficulties with coordination, communication, and work-life boundary blurring. The study offers empirical support for the strategic application of FWAs and provides practical advice to IT organizations wishing to develop more responsive, productive, and employee-friendly workplaces.